STATUS MUTU DAERAH PENAMBANGAN PASIR DI PERAIRAN SUNGAI SERAYU DENGAN MENGGUNAKAN METODE STORET - Nurlinda Ayu Triwuri; Murni Handayani; Rosita Dwityaningsih (Universitas Lambung Mangkurat, 2018)
The quality of river water is strongly related to human activities in it. Changesin the condition of water quality in the river flow are the effects of the dischargefrom existing land use. One of them is sand mining activities along the SerayuRiver, especially around Tumiyang, Kebasen, Banyumas Regency. Activitiesfrom sand mining will cause a decrease in river water quality. From this activity,it is necessary to study the status of water quality using the STORET method todetermine the quality of river water so that the river can be utilized in accordancewith the applicable designation.The STORET method is one method for determining water quality data withwater quality standards in accordance with the appointment of Minister ofEnvironment Decree No.115 2003. This research is a quantitative descriptivestudy to determine the water quality of the Serayu river in the sand of miningareas precisely in Banyumas Regency. The parameters measured in this studywere measurements of Total Disolved Solid (TDS), temperature, pH, andElectrical Conductivity. Determining the location of taking water using apurposive sampling method.Based on the results of data analysis using the Storet method and refers to thequality standards of Government Regulation No.20 of 1990 Group D. Waterquality in Serayu River has a total score of 9 after sand mining. This shows thequality status of the lightly polluted Serayu river (-1 to -10). But still in class Band the river water quality level is still in good condition. There are temperatureparameters that exceed the threshold of 25 - 32oC, but the TDS, DHL and pHparameters are still within the threshold of designation in Group D.